Cardiac Magnetic Resonance Evaluation of Left Ventricular Myocardial Strain in Pulmonary Hypertension - Kallianos, Kimberly; Brooks, Gabriel C; Mukai, Kanae; Seguro de Carvalho, Florent; Liu, Jing; Naeger, David M; De Marco, Teresa; Ordovas, Karen G (Academic radiology, 2018)
We investigated the feasibility of detecting left ventricular (LV) cardiac magnetic resonance (CMR) strain abnormalities using feature-tracking in patients with pulmonary hypertension (PH). CMR was performed in 16 patients with all groups of PH and in 13 controls. Global and regional peak circumferential strains (%) (which have been shown to be robust by CMR), peak diastolic strain rate (%/s), and dyssynchrony index (ms) were quantified with feature-tracking software. Ventricular function and volumes were calculated from CMR, and right heart pressures were measured with catheterization. Left ventricular ejection fraction (LVEF) was similar in patients (60.2% ± 11.0%) and controls (61.9% ± 4.5%), P = .150. Global LV peak circumferential strain was significantly different in patients compared to controls, -16.7 ± 2.8% vs -19.9 ± 1.8%, respectively (P = .001). The greatest difference in strain was seen in the LV septum, -11.6 ± 4.3% in patients vs -16.7 ± 4.0% in controls (P < .001). There was a significant association between septal strain and right ventricular end-diastolic volume index (P = .047) in patients with PH; however, there were no associations with pulmonary artery pressures or right ventricular ejection fraction. Feature-tracking CMR can detect LV strain abnormalities in patients with PH and preserved or mildly depressed LVEF, with greatest abnormality in the septum. The association between septal strain and right ventricular end-diastolic volume index suggests that ventricular interdependence may be a mechanism of LV dysfunction in PH. Feature-tracking CMR may be useful for identification of LV dysfunction before LVEF significantly declines in patients with PH. The feasibility of detecting LV strain abnormalities in patients with PH shown by this study paves the way for a variety of future investigations into the applications of LV strain in this patient population.